An Analysis on Employee Training and Development Relationship and Technique In India: a Strategic Hrm Function: Exploring Training and Development Practices in Indian Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In this context, human resources are the most important asset ofstatistical offices. Appropriate and skilled human resources are essential toensure the production of high quality statistics and to implement moreefficient and effective production processes based on new technologies.Proactive human resources management is essential to achieve the abovementionedchange and to allow statistical offices to meet the challenges today and infuture. This paper highlighting good practices in human resources managementTraining and development in statistical offices. The papers cover a range ofissues from recruitment and retaining of qualified staff and setting uptraining programmes, to competence mapping and management development. Thesepapers have been presented at seminars and workshops on human resourcesmanagement and training in India. The purpose of the study was to investigate the relationship betweenTraining and Development (T&D) as a Human Resource Practice and theorganizational performance (OP) in India. The study hypothesized that; therewas a positive relationship between T&D and OP and therefore the need toinvestigate how specific the two variables relate. Today employees no longer are eager to join any new organization wheretheir knowledge and skills do not get upgraded. Providing opportunities forlearning is being used as a retention tool by large number of organizations.Attracting and retaining employees have become a challenging task in thecompetitive environment. Increase in training budget and providing propertraining have become the strategies of the best companies to magnetize, retainand get highest quality output from the employees. This article explores thetraining and development practices used by the Indian organizations foreffective utilization of its workforce.